Ethics and SARS: lessons from Toronto - Singer, Peter A (BMJ Publishing Group Ltd., 2003)
The SARS epidemic showed how easy it is for infectious diseases to spread round the world. Ethical as well as clinical issues need to be resolved to improve the response to the next epidemic